Pengadaan Alat Kesehatan Sebagai Upaya Percepatan Penanganan Corona Virus Disease 2019 (Covid-19) - Irfan Marzuqi Ridla Putra (Jurist-Diction, 2021)
AbstractEarly 2020, COVID-19 emerged in Indonesia and government declared it an emergency. So those efforts are needed to deal with COVID-19 by procuring medical devices through an emergency procurement mechanism. In procurement of medical devices, there are technical specifications that must be met, is distribution permits. Due to the limited number of medical devices used for COVID-19, Minister of Health provided relaxation in the form of releasing distribution permits, which were replaced with recommendations by BNPB. In this research, will discuss the emergency procurement procedures and BNPB's authority over the issuance of recommendations to replace distribution permits. The results of this legal research, emergency procurement in SE LKPP Number 3 of 2020 can be carried out through providers or self-management, the process starts from identifying needs to auditing. BNPB is given the authority to issue recommendations instead of a distribution permit that is valid until the emergency status is revoked.Keywords: Emergency Procurement; COVID-19; Medical Devices; Authority; Recommendations.AbstrakAwal 2020, COVID-19 muncul di Indonesia dan pemerintah menyatakannya sebagai keadaan darurat. Sehingga diperlukan upaya penanganan COVID-19 dengan pengadaan alat kesehatan melalui mekanisme pengadaan darurat. Dalam pengadaan alat kesehatan terdapat spesifikasi teknis yang harus dipenuhi yaitu izin edar. Mengingat keterbatasan alat kesehatan yang digunakan untuk COVID-19, Menteri Kesehatan memberikan relaksasi berupa pemberian izin edar, yang diganti dengan rekomendasi BNPB. Dalam penelitian ini akan dibahas prosedur pengadaan darurat dan kewenangan BNPB atas penerbitan rekomendasi penggantian izin edar. Hasil penelitian hukum ini, pengadaan darurat dalam SE LKPP Nomor 3 Tahun 2020 dapat dilakukan melalui penyedia atau swakelola, prosesnya dimulai dari identifikasi kebutuhan hingga audit. BNPB diberi kewenangan untuk mengeluarkan rekomendasi sebagai pengganti izin edar yang masih berlaku sampai status darurat dicabut.Kata Kunci: Pengadaan Darurat; COVID-19; Alat Kesehatan; Kewenangan; Rekomendasi.